Tosamaidan In Kashmir: Ecological And Economic Significance (International Journal of Food and Nutritional Sciences, 2024)
The Tosamaidan is very famous for its scenic beauty as it has been bestowed with beautiful and fascinating water bodies, snow clad mountains, lush green forests and verdant meadows, green valleys, pleasant and invigorating climate. Blessed with rich natural resources, the Tosamaidanis considered one of the most beautiful places in the Kashmir valley compared to other places. Its vast area, mesmerising water bodies, rich flora and fauna, beautiful glaciers, lakes, captivating topography, invigorating climate is unique in all respects